Dos géneros nuevos de caracoles terrestres (Stylommatophora: Arionacea) de Chile - Vargas Almonacid, Patricio (2007)
We describe two new genera of land molluscs found under wet leaf litter in isolated fragments of a secondary native forest at the Hualpén Botanical Park (36º45 ́-36º49 ́ S, 73º9 ́-73º13 ́ W), University of Concepción, Chile. The new taxa are Pichikadi gen.n., of Punctidae, and Chellius gen.n., of Charopidae, with the following new species: Pichikadi hualpensis sp.n., and Chellius piramidalis sp.n. English diagnosis are presented for all taxa, together with an English identification key and English versions of figure captions and table headings. To facilitate subsequent studies and interpretations, we follow recent authors in using mainly shell characters, an approach that has favored the present taxonomic stability of the world’s land micromollusca. The diagnosis and observations are complemented with a key for the species of these families inhabiting continental Chile.